Sufism approached in school counseling service: an analysis of perspective spiritual counseling - Al Faiz (SCHOULID: Indonesian Journal of School Counseling, 2017)
This article will provide a new paradigm of thinking and practical in counseling, it based on the needs of counseling services that have been merely empirical and determinist counseling that still do not have a good influence in helping to solve problems that occur on social, cultural, political and education phenomena in this time. Moreover, when the government provides a new curriculum 2013 that lead to the formation of character like a soft skill competencies, which is very important at this time. With a variety of social and educational problems has pushed a writer to provide a new thinking and practical in counseling with a Sufism (mysticism) approached in counseling. In this case, the approach is to have a client through a station process (levels/maqam) into enlighten character and mind. Therefore, this article will discuss a Sufism approached (mysticism) in the process of counseling services as spiritual counseling.